The Measurement of Health-Related Quality of Life of Girls with Mild to Moderate Idiopathic Scoliosis—Comparison of ISYQOL versus SRS-22 Questionnaire - Edyta Kinel (MDPI AG, 2021)
This study aimed to compare the Italian Spine Youth Quality of Life Questionnaire (ISYQOL-PL) versus the Scoliosis Research Society-22 (SRS-22) questionnaire scores evaluating the validity of the concurrent and known-groups. Eighty-one girls (mean age 13.5 ± 1.8 years) with idiopathic scoliosis (IS) with a mean Cobb angle of 31.0 (±10.0) degrees were examined, all treated with a corrective TLSO brace for an average duration of 2.6 (±1.9) years. The patients’ scores were compared as follows: (1) age: ≤13 years vs. >13 years); (2) scoliosis severity: mild (Cobb angle 10–30°) vs. moderate (Cobb angle > 30°); (3) single curve pattern vs. double curve pattern. Lin’s concordance correlation coefficient was used to evaluate the strength of the association between ISYQOL-PL and SRS-22 scores. t-tests were applied to assess if the ISYQOL-PL measure and SRS-22 total score were significantly different in the different groups of patients. The concurrent validity analysis showed a moderate correlation (Lin pccc = 0.47). The ISYQOL-PL showed a significantly better quality of life in mild than moderate scoliosis. The severity of scoliosis but not the age or the curve pattern demonstrated a direct statistically significant effect on patients’ quality of life only when evaluated using the ISYQOL-PL.